The Influence of Intellectual Capital and Leverage on Company Value with Profitability as a Mediating Variable: Empirical Study on Technology Sector Companies Listed on the Indonesia Stock Exchange for the Period 2021-2023 - Nababan, Carmelita; Wiralestari, Wiralestari; Tiswiyanti, Wiwik (PT. Riset Press International, 2025)
This research is intended to investigate how intellectual capital and leverage impact firm value, with profitability acting as a mediating factor (focused on technology companies listed on the Indonesia Stock Exchange from 2021 to 2023). The variables examined in this study include intellectual capital and leverage as independent factors, firm value as the dependent factor, and profitability as the mediating factor. This research is categorized as quantitative. The study's population is made up of companies within the technology sector listed on the Indonesia Stock Exchange during the years 2021 to 2023. A purposive sampling method was utilized to select a sample of 20 companies. The analysis of the data was conducted using multiple linear regression through the IBM SPSS version 27 software. The data sourced for this research are secondary data retrieved from the official website of the Indonesia Stock Exchange. The results of this study reveal that intellectual capital, leverage, and profitability collectively influence financial distress. Furthermore, when considered individually, it is found that intellectual capital does not influence the company's value, leverage positively affects the company's value, profitability negatively impacts the company's value, intellectual capital positively influences profitability, leverage does not affect profitability, intellectual capital negatively influences the company's value when mediated by profitability, and leverage does not impact the company's value when mediated by profitability.